A CRITICAL REVIEW OF THE APPLICATION OF WITCHCRAFT LAWS IN THE NEW CRIMINAL CODE (EXPLORING THE IMPLICATIONS OF ARTICLE 252 OF LAW 1 2023 AND ITS IMPACT ON THE JUDICIAL SYSTEM IN INDONESIA) - Syam, Elvi Susanti; Jambak, Fachmi; Rustan, Ahmad; Herman, Herman; Mahka, Fachrur Razy (Faculty of Law, Universitas Pekalongan, 2024)
This study intends to assess the legal effects and effectiveness of the application of sanctions against witchcraft offenses under Article 252 of law no. 1 year 2023 in the social and legal setting in Indonesia. The study primarily concentrated on the regulation of witchcraft offenses within the new criminal legislation, the issues associated with proof, and the societal ramifications of enforcing these penalties. The study method adopted is normative legal method with descriptive-analytical approach. The data sources comprise main and secondary legal literature, encompassing statutes, books, scholarly journals, and pertinent articles. The findings indicate that while Article 252 of legislation 1/2023 establishes a legal foundation for activities concerning supernatural powers, the implementation of this article encounters significant obstacles, particularly with evidentiary requirements. The formal offense established in this article does not require proof of the manifestation of physical or mental repercussions, but rather stresses the declaration of the perpetrator who has supernatural powers. On the other hand, there is the potential for abuse of this item in society, which might generate horizontal disputes. The efficacy of sanction implementation relies on the accurate comprehension of its boundaries and objectives by law enforcement authorities and the public.